Effect of age on transcranial Doppler velocities in patients with aneurysmal subarachnoid hemorrhage - Ferreira Da Silva, Ivan Rocha (Eur Neurol, 2016)
BACKGROUND: It is not well understood whether age impacts transcranial Doppler (TCD) mean flow velocities (MFV) in patients with aneurysmal subarachnoid hemorrhage (SAH) with or without delayed cerebral ischemia (DCI). The aim of our study was to analyze the behavior of TCD MFV during the first 7 days after SAH in patients of different ages and correlate them with the occurrence of DCI. METHODS: Databank analysis of patients with SAH admitted between 2010– 2012 in a single center. We analyzed mean MFV of bilateral middle cerebral arteries in all patients enrolled in the study on days 1, 3 and 7. The correlation between age and TCD MFV was analyzed using a univariate linear regression model. RESULTS: 55 patients were studied. Starting on the 3rd day after the bleeding, increasing age was associated with slower MFV velocities. This trend was not affected by the interrogation of the right or left MCA. After correction to include only patients who developed DCI, the same findings persisted on days 3 and 7. CONCLUSION: Older age was correlated with a significant decrease on TCD velocities in patients with SAH, even after correction for patients who developed DCI.